Airway microbiome-immune crosstalk in chronic obstructive pulmonary disease - Kayongo, Alex; Robertson, Nicole M.; Siddharthan, Trishul; Ntayi, Moses Levi; Ndawula, Josephine Caren; Sande, Obondo J.; Bagaya, Bernard S.; Kirenga, Bruce; Mayanja-Kizza, Harriet; Joloba, Moses L.; Forslund, Sofia K. (Frontiers in Immunology, 2023)
Chronic Obstructive Pulmonary Disease (COPD) has significantly contributed to global mortality, with three million deaths reported annually. This impact is expected to increase over the next 40 years, with approximately 5 million people predicted to succumb to COPD-related deaths annually. Immune mechanisms driving disease progression have not been fully elucidated. Airway microbiota have been implicated. However, it is still unclear how changes in the airway microbiome drive persistent immune activation and consequent lung damage. Mechanisms mediating microbiome-immune crosstalk in the airways remain unclear. In this review, we examine how dysbiosis mediates airway inflammation in COPD. We give a detailed account of how airway commensal bacteria interact with the mucosal innate and adaptive immune system to regulate immune responses in healthy or diseased airways. Immune-phenotyping airway microbiota could advance COPD immunotherapeutics and identify key open questions that future research must address to further such translation.